(untitled) - 1950-; Short, Martin; 1945-; Martin, Steve; Landis, John; Jr.; Folsey, George; 1944; Michaels, Lorne; 1950- (Distributed by Warner Home Video, 2009)
The Three Amigos, a silent screen comedy act, arrive in a remote Mexican hamlet for what they think is a lucrative personal appearance, only to discover that they are expected to save the village from a terrorizing gang of bandits.
Keywords: Comedians; Drama; Brigands and robbers; Drama; Outlaws; Drama; Mexico; Drama; Films for the hearing impaired; Feature films; Comedy films